Sequencing and analysis of the complete mitochondrial genome of Coenobita brevimanus. Issue 2 (3rd July 2019) - Wang, Qi; Li, Yunjie; Tang, Dan; Wang, Jie; Xu, Jiayan; Xu, Xinyi; Wang, Zhengfei
Abstract: Coenobitidae is one of the most important families in Anomura. However, systematic classification and taxonomic studies are still limited. In this study, we determined the complete mitochondrial genome (mitogenome) of Coenobita brevimanus and further explored the phylogenetic relationships of Anomura. In the whole mitogenome of C. brevimanus (16388 bp), the AT-skew is negative and the GC-skew is positive.The phylogenetic tree was constructed using MrBayes method based on the 13 PCGs, which showed that Coenobitidae is monophyletic with maximal support value. Our phylogenetic analysis can be used to provide a basis for studies of the mitochondrial evolution of Anomura.